Research on the International Standards of Fully Automatic Operation System in Urban Rail Transit - WEN Zheng; WU Weiping; LU Xiangyang (Kongzhi Yu Xinxi Jishu)
The international standards IEEE 1474 and IEC 62290 for fully automatic operation (FAO) systems in urban rail transit were respectively set by IEEE-SA (institute of electrical and electronics engineers-standard association) and IEC (international electrotechnical commission) in 1999 and 2004. These two standards are different but related. In this paper, the working progress, relevance, the driverless definition, application scope, architecture, functional requirements and focus issues of IEC 62290 and IEEE 1474 are compared and analyzed respectively. IEEE 1474 is the theoretical foundation for research and development personnel in the field of railway signaling, which is applicable to operation control systems of urban rail transit, trunk railways and medium to high speed maglev, and IEC 62290 is more suitable for FAO systems in urban rail transit.